Fitness profiling on different positions among male hockey players in Pahang sports school / Nur Fatinah Mohamed Fauzi - Mohamed Fauzi, Nur Fatinah (Faculty of Sport Science and Recreation, 2019)
The purpose of this study was to identify the differences of body composition, strength, power, speed, agility and V02 max between positions among field hockey players. Several players from Pahang Sports School from each position (n=35) were selected thru purposive sampling technique and they will be divided into 3 groups according to their positions. Anthropometric measurements were conducted and followed by other fitness components. The components were measured using BIA (Body Fat Percentage), Handgrip Strength Test (Strength), Standing Broad Jump (Power), T test (Agility), and Beep Test (V02 max) respectively. Statistical analysis of One - Way ANOVA was applied for the comparison between groups. There were no-significant differences in term of Body Composition, Handgrip Strength Test, Standing Broad Jump, Agility T Test, and Beep Test among three groups. Hence, it was concluded that body composition, strength, power, agility, and V02 max showed no differences among the three positions.